2016
DOI: 10.36725/agries.v2i1.186
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade De Cultivares De Mandioca Sob Déficit Hídrico

Abstract: O presente estudo teve como objetivo avaliar o crescimento e a produtividade de cultivares de mandioca sob déficit hídrico. O experimento foi conduzido no campo experimental da Universidade Estadual de Goiás, Câmpus Ipameri. A área experimental possui Latossolo vermelho-amarelo. O experimento foi montado seguindo o delineamento em blocos casualizados, em arranjo fatorial 4x2, utilizando quatro cultivares de mandioca (BRS 396, BRS 397, BRS 398, BRS 399) desenvolvidos pela Embrapa Cerrados e dois suprimentos híd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Studies involving genotypic characteristics of species of the Manihot genus are scarce in the literature; however, parameters such as plant height can be important for quantification of genetic diversity and selection and identification of water deficit-tolerant plants (OKOGBENIN et al, 2013), because it is essential for the evaluation of yield in several crops. Matos et al (2016) evaluated M. esculenta under water deficit and found higher plant heights in materials subjected to water stress, especially for the BRS 399 and BRS 398 cultivars. Oliveira et al (2017) evaluated 49 accessions of M. esculenta and observed that taller plants tend to be more susceptible to water stress.…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving genotypic characteristics of species of the Manihot genus are scarce in the literature; however, parameters such as plant height can be important for quantification of genetic diversity and selection and identification of water deficit-tolerant plants (OKOGBENIN et al, 2013), because it is essential for the evaluation of yield in several crops. Matos et al (2016) evaluated M. esculenta under water deficit and found higher plant heights in materials subjected to water stress, especially for the BRS 399 and BRS 398 cultivars. Oliveira et al (2017) evaluated 49 accessions of M. esculenta and observed that taller plants tend to be more susceptible to water stress.…”
Section: Resultsmentioning
confidence: 99%